Emissions estimation for lignite-fired power plants in Turkey - Vardar, Nurten; Yumurtaci, Zehra (ELSEVIER SCI LTD, 2010)
The major gaseous emissions (e.g. sulfur dioxides, nitrogen oxides, carbon dioxide, and carbon monoxide), some various organic emissions (e.g. benzene, toluene and xylenes) and some trace metals (e.g. arsenic, cobalt, chromium, manganese and nickel) generated from lignite-fired power plants in Turkey are estimated. The estimations are made separately for each one of the thirteen plants that produced electricity in 2007, because the lignite-fired thermal plants in Turkey are installed near the regions where the lignite is mined, and characteristics and composition of lignite used in each power plant are quite different from a region to another. Emission factors methodology is used for the estimations. The emission factors obtained from well-known literature are then modified depending on local moisture content of lignite. Emission rates and specific emissions (per MWh) of the pollutants from the plants having no electrostatic precipitators and flue -gas desulfurization systems are found to be higher than emissions from the plants having electrostatic precipitators and flue -gas desulfurization systems. Finally a projection for the future emissions due to lignite-based power plants is given. Predicted demand for the increasing generation capacity based on the lignite-fired thermal power plant, from 2008 to 2017 is around 30%. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Electricity; Lignite; Emissions; POLYCYCLIC AROMATIC-HYDROCARBONS; AIR-POLLUTANT EMISSIONS; CO2 EMISSION; COAL; GENERATION; IMPACTS; ENERGY; GAS; PROJECTIONS; QUALITY; Business & Economics; Energy & Fuels; Environmental Sciences & Ecology